Deterioration mechanisms in dragline wire ropes - Dayawansa, D; Kuruppu, Mahinda; Mashiri, F (Trans Tech Publications Inc, 2008)
Failures in hoist and drag ropes are studied and described based on site inspections on Marion and BE draglines. Causes of the failures are discussed. Some of the analyses of the wire rope failures centres on the wire rope accessories through which these ropes travel during machine operation. The influence of wire quality on wire rope life is also studied. Visual and metallographic examinations are both used in this study leading to a better understanding of deterioration mechanisms that lead to failure of hoist and drag ropes under service loading.